Upper-body repeated-sprint training in hypoxia in international rugby union players - Beard, A.; Ashby, J.; Kilgallon, M.; Brocherie, F.; Millet, G. P. (European Journal of Sport Science, 2019)
This study investigated the effects of upper-body repeated-sprint training in hypoxia vs. in normoxia on world-level male rugby union players` repeated-sprint ability (RSA) during an international competition period. Thirty-six players belonging to an international rugby union male national team performed over a 2-week period four sessions of double poling repeated-sprints (consisting of 3 × eight 10-s sprints with 20-s passive recovery) either in normobaric hypoxia (RSH, simulated altitude 3000 m, n = 18) or in normoxia (RSN, 300 m; n = 18). At pre- and post-training intervention, RSA was evaluated using a double-poling repeated-sprint test (6 × 10-s maximal sprint with 20-s passive recovery) performed in normoxia. Significant interaction effects (P < 0.05) between condition and time were found for RSA-related parameters. Compared to Pre-, peak power significantly improved at post- in RSH (423 ± 52 vs. 465 ± 69 W, P = 0.002, ²=0.12) but not in RSN (395 ± 65 vs. 397 ± 57 W). Averaged mean power was also significantly enhanced from pre- to post-intervention in RSH (351 ± 41 vs. 388 ± 53 W, P < 0.001, ²=0.15), while it remained unchanged in RSN (327 ± 49 vs. 327 ± 43 W). No significant change in sprint decrement (P = 0.151, ²?=?0.02) was observed in RSH (-17 ± 2% vs. -16 ± 3%) nor RSN (-17 ± 2% vs. -18 ± 4%). This study showed that only four upper-body RSH sessions were beneficial in enhancing repeated power production in international rugby union players. Although the improvement from RSA to game behaviour remains unclear, this finding appears of practical relevance since only a short preparation window is available prior to international games.